2000
DOI: 10.1002/1520-6807(200007)37:4<349::aid-pits5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Getting remedial mathematics students to prefer homework with 20% and 40% more problems: An investigation of the strength of the interspersing procedure

Abstract: High school students in remedial mathematics classes were exposed to three pairs of mathematics computation assignments. Three of the assignments served as control assignments and contained 15 target problems (i.e., three-digit by two-digit multiplication problems). Students were also exposed to three paired experimental assignments that contained either 15 (0% more), 18 (20% more), or 21 (40% more) equivalent target problems. Each experimental assignment was also lengthened by interspersing additional one-dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 87 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…More specifically, as Smolira (2008) argues, homework is useful in encouraging student learning, increasing their understanding of the material and enhancing their attention in class. Assigning schoolwork to students does not simply improve student academic achievement; it also helps to develop skills related to their responsibility, learning autonomy, and time management (Eaton et al, 2014;Warton, 2001), especially when students actively engage in assigned tasks (Cates & Skinner, 2000).…”
Section: Perceptions Of Homework Assignmentsmentioning
confidence: 99%
“…More specifically, as Smolira (2008) argues, homework is useful in encouraging student learning, increasing their understanding of the material and enhancing their attention in class. Assigning schoolwork to students does not simply improve student academic achievement; it also helps to develop skills related to their responsibility, learning autonomy, and time management (Eaton et al, 2014;Warton, 2001), especially when students actively engage in assigned tasks (Cates & Skinner, 2000).…”
Section: Perceptions Of Homework Assignmentsmentioning
confidence: 99%
“…Researchers have shown that, when given the choice of two academic behaviors, students will choose the academic behaviors that require the least effort (Billington, Skinner, & Cruchon, 2004; Billington, Skinner, Hutchins, & Malone, 2004; Martin, Skinner, & Neddenriep, 2001). Furthermore, as the difference in relative effort increases, so does the probability of students choosing to engage in the less‐effortful academic activity (Billington & Ditommaso, 2003; Billington & Skinner, 2002; Cates & Skinner, 2000). When providing students with a choice of reading material, they may be more likely to choose material that requires less effort to read (Skinner et al, 2005).…”
Section: Allowing Students To Choose Workmentioning
confidence: 99%
“…One strategy to increase the probability of students choosing to engage in academic behaviors that require more effort than competing behaviors (e.g., staring out the window) is to strengthen the reinforcement for those behaviors. Specifically, educators can increase the probability of students choosing to engage in high‐effort assignments by enhancing the rate, quality, and immediacy of reinforcement (Billington et al, 2004; Cates & Skinner, 2000; Mace, Neef, Shade, & Mauro, 1996; Meadows & Skinner, 2005; Neef, Mace, & Shade, 1993; Neef, Shade, & Miller, 1994). These findings suggest that an interaction between reading skill development (e.g., reading fluency) and reinforcement (intrinsic and extrinsic) can have a strong influence on student reading behavior (Skinner, 1998; Skinner, Williams, & Neddenriep, 2004).…”
Section: Allowing Students To Choose Workmentioning
confidence: 99%
“…Subsequent studies showed that interspersing additional brief problems caused students to prefer assignments with more, longer target problems (Cates & Skinner, 2000;Cates et al, in press). For example, Cates and Skinner (2000) exposed remedial mathematics secondary students to control assignments with 15 3 3 2 problems and experimental assignments with 18 and 21 3 3 2 problems and 1 3 1 problems interspersed following every third 3 3 2 problem.…”
Section: Applications Of the Interspersal Proceduresmentioning
confidence: 99%